Analisis Perpindahan Panas pada Kolektor Pemanas Air Tenaga Surya dengan Turbulence Enhancer - Ramadhan, Muhammad Nizar; Soeparman, Sudjito; Widodo, Agung Sugeng (Rekayasa Mesin, 2017)
One of the solar energy utilization is solar water heater. To improve the performance of solar water heater, modifications were applied to dual absorber plate and flow channels to increase heat absorption. The aim of this study is to analyze the heat transfer of the collector solar water heater with additional modifications turbulence enhancer. Flowrate of water were varied to 1500 ml/min, 1200 ml/min, 900 ml/min, and 700 ml/min. The result shown that Â the highest collector energy loss (Qloss) and useful energy (Qu) are 92.23 Watt and 653.83 Watt, respectively, in a Â volume flow rate of 700 ml/min and the total solar radiation of 672.78 W/m2. The useful energy (Qu) increase with reducing the volume flow rate of water. This is due to by reducing the volume flow rate, the heated water will expose longer to absorb the heat from absorber plate.